2014
DOI: 10.1111/jvim.12452
|View full text |Cite
|
Sign up to set email alerts
|

Oxidant‐Antioxidant Status in the Blood of Horses with Symptomatic Recurrent Airway Obstruction (RAO)

Abstract: BackgroundSystemic oxidative stress in horses with recurrent airway obstruction (RAO) is poorly characterized.ObjectivesThe goal of this study was to investigate whether equine RAO is associated with systemic disturbances in the oxidant‐antioxidant equilibrium.AnimalsSeven healthy horses and 7 horses with symptomatic RAO.MethodsA prospective study. Healthy and RAO‐affected horses were exposed to a 48‐hour challenge with moldy hay and straw to induce clinical exacerbation of RAO. Venous blood was collected and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 36 publications
(105 reference statements)
1
14
0
1
Order By: Relevance
“…GSH-Px reacts with oxidants such as hydrogen peroxide and lipid hydroperoxides produced in the membrane (16,22). It is believed that hydrogen peroxide, which cannot be neutralized, is increased on the membrane surface as a result of decreased GSH-Px activity (24,25). Besides, it was determined that MDA concentration, which is a marker of lipid peroxidation, was significantly higher in the dogs with non-regenerative anemia.…”
Section: Resultsmentioning
confidence: 99%
“…GSH-Px reacts with oxidants such as hydrogen peroxide and lipid hydroperoxides produced in the membrane (16,22). It is believed that hydrogen peroxide, which cannot be neutralized, is increased on the membrane surface as a result of decreased GSH-Px activity (24,25). Besides, it was determined that MDA concentration, which is a marker of lipid peroxidation, was significantly higher in the dogs with non-regenerative anemia.…”
Section: Resultsmentioning
confidence: 99%
“…In another study though, increased TNF-a concentrations were found after ex vivo stimulation with bacterial products in RAO affected horses (Lavoie-Lamoureux et al 2012b). Niedzwiedz et al (2011) found increased markers for oxidative stress in peripheral blood during exacerbation compared to controls.…”
Section: Systemic Inflammatory Markers In the Bloodmentioning
confidence: 90%
“…Antioxidant enzymes in horse pathology have been described, among others, in the course of oxidative stress following (62,63). Authors compare enzyme activity in a group of horses with RAO and those clinically healthy (64). The results of these studies showed a significantly impaired activity of antioxidant enzymes in horses with clinical form of RAO.…”
Section: The Enzyme Triad In Raomentioning
confidence: 99%
“…This condition indicates intensified formation of free radicals and their active participation in the pathogenesis of recurrent airway obstruction. Some studies showed a statistically significant increase in the activity of antioxidant enzymes in ill horses, while other studies showed a decrease in activity of these enzymes (18,22). Inconsistent results may be associated with the exacerbation of symptoms, horse maintenance or any treatment administered (1).…”
Section: The Enzyme Triad In Raomentioning
confidence: 99%
See 1 more Smart Citation